Continuity defects of the mandible: Comparison of three techniques for osseous reconstruction and their impact on implant loading. Issue 5 (May 2018) - Okcu, Yunus; Rustemeyer, Jan
Abstract: Computer-aided design/manufacturing (CAD/CAM) is now widely used, but whether it can help to overcome complications in mandibular reconstruction and accelerate dental implantation is still a matter for debate. Therefore, we aimed to evaluate the benefits of this technique using vascularized iliac crest or fibula flaps in mandibular reconstruction, with respect to the time between reconstruction and implantation, and the ratio of planned to inserted implants. We reviewed retrospectively the records of 54 patients who underwent mandibular reconstructions between 2012 and 2016, and included in our study the last 10 cases representing each of the following groups: iliac crest flap with CAD/CAM (Group 1); fibula flap with CAD/CAM (Group 2); and fibula flap without CAD/CAM (Group 3). Groups 1 ( p = 0.045) and 2 ( p = 0.034) showed significantly shorter delays when compared with Group 3. Significant differences in average counts of implants placed were also found between Group 1 and Groups 2 ( p = 0.04) and 3 ( p = 0.019). The ratio of planned to placed implants was highest in Group 1. The observed differences between Group 1 and Groups 2 ( p = 0.04) and 3 ( p = 0.019) were significant. Our results indicate an accelerating effect of CAD/CAM on graft consolidation and dental rehabilitation.